Paleotectonics of a complex Miocene half graben formed above a detachment fault: The Diligencia basin, Orocopia Mountains, southern California - Caracciolo, Luca; et al. (Lithosphere, 2014)
These palinspastic restorations result in a coherent set of SW-NE-trending normal faults, basins (including Diligenica basin) and antiformal structures consistent with NW-SE-directed crustal extension from 24 to 18 Ma, likely resulting from the unstable configuration of the Mendocino triple junction.